Free space optical communication system for indoor applications based on printed circuit board design - Alsharef Mohammad; Mohammed S. Alzaidi; Mahmoud M. A. Eid; Vishal Sorathiya; Sunil Lavadiya; Shobhit K. Patel; Ahmed Nabih Zaki Rashed (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
This study clarified an overview of wired and wireless optical communication system block diagram with practical applications. Freespace optical (FSO) communication is a trending field that is rising so fast to replace electromagnetic waves in a communication, so we have presented a theoretical circuit as an example and modified it to fit and work in communication purposes, simulation is used and then practical work is done and printed circuit board (PCB) is designed. Light emitting diode (LED) have been used as transmitter and Photo Transistor as a receiver and variable resistance to change voltage sent to the LED that indicates the change in the transmitted signal.